Explantation and reimplantation of a breast implant to facilitate minimally invasive mitral valve surgery and cryoablation of atrial fibrillation - Ayse Cetinkaya; André Borsche; Stefan Hein; Peter Bramlage; Markus Schoenburg; Manfred Richter (Clinical Case Reports, 2019)
Abstract Clinicians can feel confident about performing mitral repair/replacement in patients who have previously undergone mammoplasty. It may also have applications in performing atrial septal defect closure, Maze procedures for atrial fibrillation, and tricuspid valve surgery in patients with breast implants.